Reconceptualizing the Digital Humanities in Asia - Kung, Kaby Wing-sze (Springer Singapore Pte. Limited, 2020)
Intro – Series Preface – Acknowledgements – Introduction: Reconceptualization of the Humanities in the Digital Age – References – Contents – Part IArt and Film in the Digital Age – 1 Museum Narration: A Memory-Driven Storyscape – Introduction – The Museum as an Institute of Collective Memory – Memory-Driven Storyscapes in Museums – Architectural Narratives – Exhibition Narratives –
Description based on publisher supplied metadata and other sources
Keywords: Digital humanities; Humanities-Research-Asia; Electronic books